Post-Pandemic Marketing Management Strategy Based on Fishbone Analysis in Kampung Inggris Pare, Kediri Regency - Permatasari, Indah; Hidyatullah, Ahmad Taufiq; Paulus, Johanes Christian (A Social Science and Entrepreneurship Journal, 2023)
This research was conducted to dig out the root causes of ineffectiveness of marketing strategies implemented in English Educational Tourism Village in Pare, Kediri Regency and find the recommendations for them, specifically post-pandemic context. This research using a qualitative descriptive method, then, analyzed using a fishbone diagram.  The result depicted English courses in Pare, Kediri did not well implement marketing strategies, specifically digitally. It was because of lacking knowledge and skills regarding business management, less capital and lacking high-quality human resources needed. In general, researchers gave some recommendations for evaluating marketing strategies such as : 1) Implementing Segmenting, Targeting, Positioning (STP) strategies, 2) Digitalizing marketing strategies 3) Gaining more capital, 4) Upscaling human resource competencies.